PubChem BioAssay: A Decade's Development toward Open High-Throughput Screening Data Sharing. (July 2017) - Wang, Yanli; Cheng, Tiejun; Bryant, Stephen H.
High-throughput screening (HTS) is now routinely conducted for drug discovery by both pharmaceutical companies and screening centers at academic institutions and universities. Rapid advance in assay development, robot automation, and computer technology has led to the generation of terabytes of data in screening laboratories. Despite the technology development toward HTS productivity, fewer efforts were devoted to HTS data integration and sharing. As a result, the huge amount of HTS data was rarely made available to the public. To fill this gap, the PubChem BioAssay database (https://www.ncbi.nlm.nih.gov/pcassay/ ) was set up in 2004 to provide open access to the screening results tested on chemicals and RNAi reagents. With more than 10 years' development and contributions from the community, PubChem has now become the largest public repository for chemical structures and biological data, which provides an information platform to worldwide researchers supporting drug development, medicinal chemistry study, and chemical biology research. This work presents a review of the HTS data content in the PubChem BioAssay database and the progress of data deposition to stimulate knowledge discovery and data sharing. It also provides a description of the database's data standard and basic utilities facilitating information access and use for new users.